2015
DOI: 10.1002/jbmr.2596
|View full text |Cite
|
Sign up to set email alerts
|

Fat and Sucrose Intake Induces Obesity-Related Bone Metabolism Disturbances: Kinetic and Reversibility Studies in Growing and Adult Rats

Abstract: Metabolic and bone effects were investigated in growing (G, n ¼ 45) and mature (M, n ¼ 45) rats fed a high-fat/high-sucrose diet (HFS) isocaloric to the chow diet of controls (C, n ¼ 30 per group). At week 19, a subset of 15 rats in each group (HFS or C, at both ages) was analyzed. Then one-half of the remaining 30 HFS rats in each groups continued HFS and one-half were shifted to C until week 27. Although no serum or bone marrow inflammation was seen, HFS increased visceral fat, serum leptin and insulin at we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 92 publications
4
19
0
2
Order By: Relevance
“…As in long bones, bone microarchitecture analysis is relevant in ankle bones. Parameter values were comparable with studies in femur or lumbar vertebrae (Lavet et al, ). Then we demonstrated that navicular bone was the most reproducible for measurement and the most sensitive to arthritis, as previously suggested by histological analysis performed only on navicular bones after arthritis onset (Schett et al, ), for two reasons suggested by our results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As in long bones, bone microarchitecture analysis is relevant in ankle bones. Parameter values were comparable with studies in femur or lumbar vertebrae (Lavet et al, ). Then we demonstrated that navicular bone was the most reproducible for measurement and the most sensitive to arthritis, as previously suggested by histological analysis performed only on navicular bones after arthritis onset (Schett et al, ), for two reasons suggested by our results.…”
Section: Discussionsupporting
confidence: 87%
“…Trabecular changes were also described and more significant in quantification compared to cortical changes. They may be related to fast trabecular remodeling compared to cortical remodeling (Lavet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing and mature rats ingested an isocaloric HFS diet for 19 and 27 weeks to induce obesity-related bone metabolism disorder [21], and it was observed that the HFS diet seemed to favor trabecular bone mass, while cortical thickness, along with density, did not obviously change.…”
Section: Studies In Animalsmentioning
confidence: 99%
“…(7,8) Similarly, in rodents, we and others have demonstrated that short-term high-fat feeding is associated with preserved or increased bone density. (9)(10)(11) There are studies that support a negative impact of obesity on bone quantity (12)(13)(14) or its biomechanical properties, (15,16) leading to the thinking that, despite increased bone quantity in the setting of obesity, bone quality and composition may not be commensurate to body weight, even representing relative bone fragility and increased fracture risk. (17,18) Further, obesity has been associated with increased fractures, albeit not classic osteoporotic fragility fractures.…”
Section: Introductionmentioning
confidence: 99%